I rapporti con la corte francese dell’Arlecchino Tristano Martinelli nelle 'Compositions de rhétorique' (1600-1601) - Berger, Cécile (Incontri. Rivista europea di studi italiani, 2018)
The Arlecchino Tristano Martinelli’s relationship with the Royal French Court, in the Compositions de rhétorique (1600-1601)The purpose of this paper is to examine the development and context of the Compositions de rhétorique by Tristano Martinelli between October 1600 and 17 January 1601. This work is nowadays conserved in one single copy, stored at the Bibliothèque Nationale de France. The book was published on the occasion of the royal wedding between King Henry IV of Navarre and Maria de’ Medici, officiated on 17 December 1600 in Lyon. For exceptional occasions of this kind, the French Court often invited Italian comedians since the 1570s. At the same time, most of them took advantage of their presence in France to publish personal works, mainly comedies and theoretical writings about comedy. In this case, the famous comedian Tristano Martinelli, known as the first and best Arlecchino ever, published a book that is half empty, containing only a few printed pages. The analysis of its printed pages sheds light on Tristano Martinelli’s personality, but also on the unique relationship between this actor from the commedia dell’arte and the King and Queen of France.